Analysis of Rice-Business Insurance Program (Autp) In Ponorogo District (Case Study In Agriculture And Fisheries Department of Ponorogo District Work Program 2018-2019) - Samidi; Ahsin Daroini; Abu Talhah (Agricultural Science, 2019)
This research aimed: (a) to analyze the implementation of rice farm business insurance (AUTP) in the Ponorogo District Work Area; (b) to find out the factors that influence the implementation of the AUTP program in Ponorogo district; (c) to prove that the agricultural sector in Ponorogo district is a base and superior sector. This research uses a qualitative approach, where the reality under study is understood by a holistic approach and does not take measurements on certain parts of the reality. This study uses Internal Factor Analysis, External Factor Analysis, Klassen Typology and LQ (Location Quetiont) Analysis. The results of the research show that: (a) Implementation of AUTP in Ponorogo district cannot be said be maximal. This is reinforced by the results of the typology Klassen analysis in Ponorogo district in the "Inactive" category; (b) Based on the results of the analysis of internal factors in this study, it was found that the implementation of the AUTP program in Ponorogo district found weaknesses and strengths that influenced the responses of farmers in Ponorogo Regency. The agricultural sector in Ponorogo Regency is a base and superior sector. (c) Based on the results of the study it was found that the LQ (Location Quantient) value from 2016 to 2018 obtained the value of LQ> 1, this indicates that the agricultural sector becomes the base and superior sector in Ponorogo district. With the knowledge of agriculture as a base sector, inputs can be produced so that the agricultural sector remains the Ponorogo base sector.